Pengaruh Electronic Word of Mouth (E-Wom) dan Fasilitas Terhadap Keputusan Berkunjung di Panorama Tabek Patah - Wira Tri Annisa; Youmil Abrian (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
Several issues with the title serve as the impetus for this study. The purpose of this study is to examine the impact of amenities and Electronic Word of Mouth (E-Wom) on the choice to visit Panorama Tabek Patah. In this study, a descriptive, quantitative research design was adopted. Primary data is the kind of data used in this study. Visitors to Panorama Tabek Patah are the study's participants. Using a non-probability sampling technique, 110 customers comprised the research sample. A Likert scale questionnaire that had undergone validity and reliability testing was used in the data collection process. SPSS 25.00 was used to process the data from this study. The facilities fall within the sufficient category, according to the research's findings. With a value of 3.21, the electronic word-of-mouth (E-WOM) variable displays the sufficient category. The facility variable, which equals 3.26, displays the sufficient category. With a value of 3.26, the visiting decision variable displays the sufficient category. Facilities and electronic word-of-mouth (E-WOM) have a 20% impact on travel decisions, while a number of other elements, including location, image/brand, price/tariff, and service, have an 80% influence.